Temporal trends of legacy and novel brominated flame retardants in sediments along the Rhône River corridor in France. (May 2021) - Vauclin, Sophia; Mourier, Brice; Dendievel, André-Marie; Marchand, Philippe; Vénisseau, Anaïs; Morereau, Amandine; Lepage, Hugo; Eyrolle, Frédérique; Winiarski, Thierry
Abstract: Brominated flame retardants (BFRs) are anthropogenic compounds that are ubiquitous in most manufactured goods. Few legacy BFRs have been recognised as persistent organic pollutants (POPs) and have been prohibited since the 2000s. However, most BFRs continue to be used despite growing concerns regarding their toxicity; they are often referred to as novel BFRs (nBFRs). While environmental contamination due to chlorinated POPs has been extensively investigated, the levels and spatiotemporal trends of BFRs are comparatively understudied. This study aims to reconstruct the temporal trends of both legacy and novel BFRs at the scale of a river corridor. To this end, sediment cores were sampled from backwater areas in four reaches along the Rhône River. Age-depth models were established for each of them. Polychlorinated biphenyls (PCBs), legacy BFRs (polybrominated diphenyl ethers - PBDEs, polybrominated biphenyls - PBBs and hexabromocyclododecane - HBCDDs) and seven nBFRs were quantified. Starting from the 1970s, a decreasing contamination trend was observed for PCBs. Temporal trends for legacy BFRs revealed that they reached peak concentrations from the mid-1970s to the mid-2000s, and stable concentrations by the mid-2010s. Additionally, individual concentrations of nBFRs were two to four orders of magnitude lower than those of legacy BFRs. Their temporal trends revealed that they appeared in the environment in the 1970s and 1980s. The concentrations of most of these nBFRs have not decreased in recent years. Thus, there is a need to comprehend the sources, contamination load, repartition in the environment, and toxicity of nBFRs before their concentrations reach hazardous levels. Highlights: Time trends of legacy BFRs in sediments along the Rhône River are similar. Legacy BFRs reached their peak between the 1970s and the 2000s, and are now stable. nBFRs concentrations are two to four times lower than that of legacy BFRs. Some nBFRs appeared along the Rhône River as early as the 1970s–1980s. No decreasing trend in nBFRs concentrations has been observed, so far.